Use of Automated Breast Ultrasound System for 3D Imaging. - Sampson, Tara (Radiologic Technology)
The article focuses on the use of the Automated Breast Ultrasound System (ABUS) as an advanced, radiation-free 3D imaging tool that enhances breast cancer screening, particularly for women with dense breast tissue. ABUS improves visualization through coronal plane imaging, increasing the detection of small and subtle masses often missed by mammography alone, and offers more consistent, reproducible imaging for follow-up examinations. It is also presented as a cost-effective supplemental screening option compared to magnetic resonance imaging, potentially increasing early cancer detection rates and patient confidence in routine screenings. Overall, ABUS supports radiologists and technologists in providing higher-quality, standardized breast imaging and improved diagnostic outcomes.